The importance and distribution of green spaces and their design systems in cities (The City of Alamara Case Study) - Almusawi, Mohammed Arab (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the form of geographic extent of green spaces and the actual high density Centre of population and urbanism and the expected one. Also, the study aims to identify the connection of green spaces with population distribution and urban extent in addition to the suitability of their characteristics and advantages in the city according to the two domestic and global standards. The questionnaire was randomly distributed to a sample of 15521 people, 2 percent of the total number of families in the city of Amara which was 77646 families as estimated by the Central Statistical Organization in 2018. The study has a group of conclusions and recommendations, the most important of which are the lack of investment awareness in the field of gardens and public parks in addition to the lack of economic return estimate of green spaces. Also, the city of Amara has planning problems in using green spaces because of the spatial variation among the city areas and its residential stores